2020
DOI: 10.3390/nu12051502
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Efficacy of a Milk Permeate-Based Oral Hydration Solution

Abstract: Milk permeate is an electrolyte-rich, protein- and fat-free liquid with a similar carbohydrate and mineral content to that of milk. Its hydration efficacy has not been examined. The beverage hydration index (BHI) has been used to compare various beverages to water in terms of post-ingestion fluid balance and retention. Our purpose was to compare the BHI (and related physiological responses) of a novel milk permeate solution (MPS) to that of water and a traditional carbohydrate–electrolyte solution (CES). Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
2
16
1
Order By: Relevance
“…The BHI for a sports drink (with 3.9% carbohydrate, 21 mmol Na + ) was originally reported as not different from water [ 15 ]. The sports drink in that investigation had 33% lower carbohydrate than in the current study (but similar electrolytes); however, a 6% sports drink was later confirmed [ 16 , 19 ] to be no different from water (BHI < 1.10) in contrast to other observations [ 17 ] and those reported here indicating a higher BHI for sports drinks in young adults. Moreover, adding carbohydrate (at 3, 6, and 12%) retained more fluid compared to placebo water without electrolytes over a 4-h post-exercise rehydration period, but the carbohydrate content per se did not impact fluid retention [ 7 ].…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…The BHI for a sports drink (with 3.9% carbohydrate, 21 mmol Na + ) was originally reported as not different from water [ 15 ]. The sports drink in that investigation had 33% lower carbohydrate than in the current study (but similar electrolytes); however, a 6% sports drink was later confirmed [ 16 , 19 ] to be no different from water (BHI < 1.10) in contrast to other observations [ 17 ] and those reported here indicating a higher BHI for sports drinks in young adults. Moreover, adding carbohydrate (at 3, 6, and 12%) retained more fluid compared to placebo water without electrolytes over a 4-h post-exercise rehydration period, but the carbohydrate content per se did not impact fluid retention [ 7 ].…”
Section: Discussioncontrasting
confidence: 62%
“…The type of carbohydrate found in a beverage may also be a factor influencing the BHI. Berry et al [ 16 ] reported a milk permeate solution (devoid of fat and protein) with 4% glucose/galactose had a higher BHI (>1.2) compared to water, unlike a 6% sucrose/glucose sports drink. However, the fact that the milk permeate beverage had much higher mineral content (e.g., 28 mmol/L K + ) and nearly 300 mosmol/kg higher osmolality (with contributions from magnesium, phosphorous, calcium, and chloride) despite a similar sodium and lower carbohydrate makes it difficult to clearly differentiate the impact of the carbohydrate type on BHI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutrients may mediate and/or moderate total body water and fluid homeostasis by influencing the osmotic pathways responsible for intra- and extra-cellular fluid shifts within the body. Determining the types of nutrients that mediate and/or moderate total body water and fluid homeostasis is of continued interest within the scientific literature [ 20 , 21 , 22 , 23 ]. Within sport and exercise settings specifically, investigating how beverage composition optimizes total body water and restores body water deficits has been thoroughly investigated [ 24 ] and evidence shows that the addition of sodium [ 23 , 25 , 26 ], carbohydrates [ 27 ], and protein [ 28 , 29 ] improves water retention and restores body water lost in sweat.…”
Section: Introductionmentioning
confidence: 99%